2022
DOI: 10.1093/molbev/msac231
|View full text |Cite
|
Sign up to set email alerts
|

An Approximate Bayesian Computation Approach for Modeling Genome Rearrangements

Abstract: The inference of genome rearrangement events has been extensively studied, as they play a major role in molecular evolution. However, probabilistic evolutionary models that explicitly imitate the evolutionary dynamics of such events, as well as methods to infer model parameters, are yet to be fully utilized. Here, we developed a probabilistic approach to infer genome rearrangement rate parameters using an Approximate Bayesian Computation (ABC) framework. We developed two genome rearrangement models, a basic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The loss of synteny information with increasing rearrangement rates is hard to overcome within a parsimony-based framework, meaning that a different approach to modelling genome evolution may be required; e.g. estimating rearrangement parameters through simulation (Moshe et al . 2022) or performing a Bayesian sampling of rearrangement histories (Miklé s and Tannier 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of synteny information with increasing rearrangement rates is hard to overcome within a parsimony-based framework, meaning that a different approach to modelling genome evolution may be required; e.g. estimating rearrangement parameters through simulation (Moshe et al . 2022) or performing a Bayesian sampling of rearrangement histories (Miklé s and Tannier 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The loss of synteny information with increasing rearrangement rates is hard to overcome within a parsimony-based framework, meaning that a different approach to modelling genome evolution may be required; e.g. estimating rearrangement parameters through simulation (Moshe et al 2022) or performing a Bayesian sampling of rearrangement histories (Miklós and Tannier 2010). Interestingly, Markov models of chromosome number evolution have recently been developed (Yoshida and Kitano 2021;Setter 2023) and could be adapted to estimate model parameters and sample likely rearrangement histories given a set of genomes.…”
Section: Rearrangement Rates and Marker Errormentioning
confidence: 99%
“…Despite ABC does not require likelihood analyses, it can provide estimates with similar (sometimes higher) accuracy compared to those obtained with some likelihood-based methods ( Lopes et al 2014 ). Some previous works demonstrated that ABC can be used to study molecular evolution ( Wilson et al 2009 , Lopes et al 2014 , Arenas et al 2015a , Arenas 2015b , Moshe et al 2022 ). For example, at the protein level, we previously applied ABC to estimate substitution and recombination rates with acceptable accuracy ( Arenas 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…ABC is commonly applied when it is challenging to compute the likelihood, as this procedure bypasses the need to explicitly calculate likelihood. The ABC procedure, which was first developed in the field of population genetics ( Beaumont et al 2002 ), has been since utilized successfully in many other studies ( Przeworski 2003 , Tallmon et al 2008 , Kuhlwilm et al 2019 , Moshe et al 2022 ). Our group had previously utilized ABC for inferring the rates and length parameters of indels ( Karin et al 2017 , Loewenthal et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%